Gene polymorphism of MTHFR rs1801133 and susceptibility to childhood leukemia in Chinese population: MTHFR rs1801133 and childhood leukemia - Peng, Yin; Wu, Lin; Wang, Chengjun (Journal of Medical Biochemistry, 2023)
Background: The purpose of this study is to investigate the genotype and allele distribution of MTHFR rs1801133 in the Chinese population, and to analyze the relationship between gene polymorphism of MTHFR rs1801133 and risk of childhood leukemia. Methods: Blood samples and clinical data of childhood leukemia cases (n=1132) and age-matched healthy controls (n=1053) were collected. Genotypes and allele distribution of MTHFR rs1801133 were detected by PCR-RFLP. Logistic regression model was generated to analyze the relation between MTHFR rs1801133 and susceptibility to childhood leukemia and the chemotherapy response. Results: Age, sex, BMI and family history of tumor were comparable between childhood leukemia cases and healthy controls. Genotypes and allele distribution of MTHFR rs1801133 were remarkably correlated to the risk of childhood leukemia. Genotype risk of MTHFR rs1801133 was parallel to the susceptibility to childhood leukemia. Specifically, compared with people carrying AA allele of MTHFR rs1801133, higher risk of childhood leukemia may occur in people carrying AG+GG allele of MTHFR rs1801133 with a younger age (<15 years) or complete remission from chemotherapy. Conclusions: MTHFR rs1801133 gene polymorphism has a significant correlation with childhood leukemia. It is an important genetic susceptibility gene of childhood leukemia. The reliability of the results requires to be further validated by the high-quality research involving a large sample size in multi-center hospitals.